Camellia Sinensis (Green Tea) Health Benefits (Review) (Journal of Medical Sciences, 2023)
Tea is one of the most widely consumed beverages worldwide, and is available in various forms. Green tea is richer in antioxidants compared to other forms of tea. Tea is composed of polyphenols, caffeine, minerals, and trace amounts of vitamins, amino acids, and carbohydrates. The composition of the tea varies depending on the fermentation process employed to produce it. Camellia sinensis is a species of Camellia. Fresh leaves or a leaf extract for therapeutic use may have a variety of systemic effects on your health. Green tea includes hundreds of bioactive compounds, including tannic acid, ellagitannins, and phenols such as flavonoids and catechins, which are highly antioxidant in vitro and in vivo and virtually have polyphenols, which play a major role in preventing and treating many diseases. Green tea also contains minerals and vitamins, which boost the tea's antioxidant capacity. Furthermore, Camellia sinensis may help reduce the risk of cardiovascular disease and certain types of cancer, as well as promote oral health and other physiological functions such as antihypertensive effects, weight management, antibacterial and antiviral activity, solar protection, increased bone mineral density, and anti-fibrotic properties, according to a new study. While having all of the information from the green tea study is highly encouraging, further research is needed to fully understand its contributions to human health.